2018
DOI: 10.1039/c8ta06626d
|View full text |Cite
|
Sign up to set email alerts
|

Highly reversible and long-life cycling aqueous zinc-ion battery based on ultrathin (NH4)2V10O25·8H2O nanobelts

Abstract: For the first time ultrathin (NH4)2V10O25·8H2O nanobelts are employed as a cathode material for high-rate and durable rechargeable aqueous Zn-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(117 citation statements)
references
References 49 publications
5
110
2
Order By: Relevance
“…This process is reversible since V 4+ can be oxidized back to V 5+ at 1.6 V. It is also seen that the O 1s subpeak that is assigned to H 2 O is enhanced signicantly when the electrode is discharged to 0.2 V, suggesting that H 2 O molecules are incorporated into the host material together with Zn 2+ ion intercalation. 26,28,53 During the charge process, these H 2 O molecules are released. The incorporated H 2 O molecules within the lattice of host material can effectively shield the electrostatic eld of Zn 2+ ions that are inserted at the same time, therefore benecial to electrochemical kinetics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is reversible since V 4+ can be oxidized back to V 5+ at 1.6 V. It is also seen that the O 1s subpeak that is assigned to H 2 O is enhanced signicantly when the electrode is discharged to 0.2 V, suggesting that H 2 O molecules are incorporated into the host material together with Zn 2+ ion intercalation. 26,28,53 During the charge process, these H 2 O molecules are released. The incorporated H 2 O molecules within the lattice of host material can effectively shield the electrostatic eld of Zn 2+ ions that are inserted at the same time, therefore benecial to electrochemical kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, vanadium oxide, sulde, and vanadate cathode materials have attracted much attention since Nazar et al reported Zn 0.25 V 2 -O 5 $nH 2 O as a high-capacity ($300 mA h g À1 ) and long-life (1000 cycles) cathode material. [23][24][25][26][27][28][29][30][31] It is noteworthy that the reversible, stable, and rapid redox reactions associated with vanadium element render these materials highly appealing for AZIBs. For example, Alshareef et al developed hydrated layered Mg 2+intercalated V 2 O 5 (Mg 0.34 V 2 O 5 $0.84H 2 O) with a large interlayer spacing of 13.4Å, which enables high capacities of 353 and 264 mA h g À1 at 0.1 and 1 A g À1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…for characterization of nano-dimensions, were developed. This was done in order to understand better its structure-property relationships and the need to produce novel materials that could address the demand for economical, efficient, environment-friendly, and safe energy storage materials 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore they are considered as a favorable cathode material inthe secondary Li-ion batteries (LIBs) [1,4,7]. Recent studies have shown that vanadium oxide derivatives can also be successfully used in multivalent ion batteries, such as calcium-ion [8], magnesium-ion [9], and zinc-ion [10,11,12] batteries. Moreover NH 4 VO 3 is used as an efficient and mild catalyst for the synthesis of α-hydroxyphosphonate derivatives, which act as inhibitors of a diverse group of enzymes e.g.…”
Section: Introductionmentioning
confidence: 99%